Teachers’ Competence Developing Emotional Intelligence in Preschool Age Children - Kudriavcevaitė, Karolina; Lenkauskaite, Jurgita (Jaunųjų mokslininkų darbai, 2019)
The expression of emotions is one of the most important aspects of our life. One needs to know how to handle them, but, since emotional intelligence is not an innate ability, it is important to develop it (Kurienė, 2016). It is admitted that preschool age is the most suitable period to do it (Vaišvidienė, Gedvilienė, 2017). In order to successfully develop emotional intelligence in children, the teacher’s own competence in the subject is essential. In Lithuania, there is a lack of studies what competence, knowledge, skills, attitudes, personality traits a preschool teacher should have so as to ensure successful development of emotional intelligence in children. Thus the aim of this research was to identify what competence a preschool teacher should have so as to develop emotional intelligence in children. A semi-structured interview with 11 preschool teachers was carried out. The research data were analyzed using qualitative content analysis. The results of this empirical research showed that, according to the interviewees, it is important to notice differences among children and their abilities, encourage and motivate them, professionally communicate, develop a diverse learning environment, educational content and situations. The respondents also noted that it is important to understand the concept of emotional intelligence. The survey showed that the respondents pay least attention to the assessment of their own activities and of the learners’ progress. Thus, the effectiveness of emotional intelligence development in children has not been systemically investigated and purposefully improved. The respondents admitted that they lack competence needed to develop emotional intelligence in children. They emphasized that they should learn better notice differences among children and their abilities, encourage and motivate learners. They also noted that they should focus on the development of emotional intelligence more than of skills and attitudes. However, having admitted that they lack important competence in developing emotional intelligence in children, the respondents were still reluctant to personally improve and develop their learning to learn skills.